GROWTH INTENSITY OF PARTIAL PLANTATIONS OF COMMON OAK IN CONDITIONS OF TOTAL STAND RECONSTRUCTION IN THE FOREST-STEPPE PART OF KHARKIV REGION - Vedmid, М. M.; Musienko, S. I.; Ugarov, V. M.; Yatsenko, S. V. (Forestry and Forest Melioration, 2018)
The influence of tillage, planting material age, plant growth stimulants has been investigated and assessed for common oak growth in the partial forest plantations in the fresh site condition at the total reconstruction of stands in the southern Left-Bank Forest-Steppe. The tillage variation has not significantly affected on the growing of tree height/diameter dynamics, and the trees that grow from 4-year seedlings exceed the trees that grow from 2-year seedlings in terms of high by 7.6–9.0 % and in terms of diameter by 12.5–14.4 %. The trees, seedling roots of which have been processed by Emistim (10 mg/10 liters) before planting, were exceeding by 3.4% in height and by 12.5 % in diameter (as compared to the untreated seedling). The trees, seedling roots of which has been processed by Tryman (1000 mg/10 liters) before planting, were exceeding by 4.5 % in height and by 20.0 % in diameter. It was discovered that in the early years the plant growth stimulants (Emistim and Tryman) had more significant impact on the height growth, and in length of time the trees’ diameter growth was more intensive.